Human Resource Management in Managing Toxic Workplaces: A Conceptual Review - Fauziah Amanda; M. Chaerul Rizky; Daud Arifin; Grace Tessalonika; Sabam Parulian (Journal Of Management Analytical and Solution (JoMAS), 2026)
A toxic workplace is a critical organizational issue characterized by interpersonal conflict, bullying, and unfair managerial practices that significantly impair employee well-being and organizational performance. This study aims to analyze and synthesize the strategic roles of Human Resource Management (HRM) in preventing, managing, and transforming toxic work environments. Employing a qualitative systematic literature review approach, this study analyzed 20 peer-reviewed articles published between 2016 and 2026, drawn from Scopus, Web of Science, and Google Scholar. The theoretical framework integrates the Job Demands-Resources (JD-R) Model, Social Exchange Theory (SET), and Psychological Safety Theory to provide a multi-layered explanation of how HRM functions as both a protective and transformative organizational mechanism. The findings reveal four strategically interrelated HRM roles: (1) Prevention through value-based recruitment and transparent policies; (2) Intervention through anonymous reporting channels and conflict mediation; (3) Mitigation through Employee Assistance Programs and supportive leadership; and (4) Cultural Transformation through developmental performance appraisal and employee engagement. Theoretically, this study extends the JD-R Model to toxic workplace contexts and proposes an integrated four-role conceptual model. Practically, it offers a structured seven-step implementation framework.